(untitled) (Northern International Medical College Journal, 2015)
Background : Urinary tract infection (UTI) is one of the most important causes of morbidity and mortality in the developing countries like Bangladesh. Antimicrobial agents are the frequently used drug for its treatment. Periodic evaluation of antimicrobial activity of different antibiotics is essential as the pattern of antibiotic sensitivity may vary over periods. Increasing antibiotic resistance among urinary pathogens to commonly prescribed drugs has become a global reality today. Objective : To determine the prevalence and to find out the causative agents of UTI and their antibiotic sensitivity pattern among suspected UTI patients attending Northern International Medical College Hospital (NIMCH), Dhaka. Methods : A retrospective study was conducted at Northern International Medical College Hospital, Dhaka, Bangladesh by analyzing the records of urine samples collected for culture and sensitivity tests over a period of six months (January 2014 to June 2014). Of the total 878 clean catch mid-stream urine samples collected from suspected cases of UTI patients of all ages and both sexes. Urine specimens were cultured for isolation of microbial agents of urinary tract infection. The isolated bacteria were identified using biochemical test. The diffusion susceptibility test was used to determine susceptibility of bacterial agents to antibiotics. Computerized data was collected from Microbiology department of NIMCH and analyzed by Microsoft Excel Version 2013. Results : In this study, 182 (20.73%) out of 878 urine sample were positive for pathogenic organisms. Of the various pathogenic organisms isolated, Escherichia coli constituted for 85.16% followed by Pseudomonas sp, Acinatobactersp, Group D Streptococcus, Staphylococcus aureus, Klebsiellasp, Enterobactersp and others. E.coli was found to be most sensitive to Imipenem, Amikacin and Meropenem and resistant to most commonly used oral drugs like Azithromycin, Cefexime, cotrimoxazole and Ciprofloxacin and Levofloxacin. Conclusion : Mainly Gram negative bacilli is responsible for UTI and most frequent isolated bacteria was E-coli. The most effective antibiotics were Imipenem, Amikacin, Meropenem,all of them are parentral. Majority E-coli were resistant to commonly used oral drugs like Azithromycin, Cefexime, cotrimoxazole and Ciprofloxacin. Therefore the choice of antibiotic therapy in UTI should be depends on the local sensitivity pattern of the infecting organisms. Northern International Medical College Journal Vol.7(1) Jul 2015: 105-109